Preparation of poly(methyl methacrylate) and polystyrene composite-filled porous epoxy microparticles via in-situ suspension polymerization - Du Ngoc Uy Lan, DuNgoc, Dr. (Elsevier, 2014)
Link to publisher's homepage at http://www.sciencedirect.com/